The Effect of Marketing Mix on Purchase Decisions - Widyastuti, Ani Nor; Pujiharto, Pujiharto; Tubastuvi, Naelati; Santoso, Suryo Budi (Jurnal Manajemen Bisnis, 2020)
This research is essential to contribute to the minimarket with campus brands, which live and thrive in the campus environment to better understand the marketing mix factors that influence purchasing decisions. The campus is expected to provide a special image for consumers. This research discusses the marketing mix factors on consumer purchasing decisions in minimarkets with campus brands in the Banyumas Regency, namely Boersa Kampus (Unsoed), Top Campus (Unsoed, UMP), Kopkun Swalayan (Unsoed), Indo Kampus (STAIN), and UeMPe Mart (UMP). The factors used were the product, price, promotion, service, and place/location. The sample used amounted to 100 respondents who were consumers with more than 17 years of age. The sampling employed non-probability with a purposive sampling technique, and data analysis utilized multiple linear regression. The adjusted R-square value indicates that the dependent variable was influenced by the independent variable by 54.3%. The results showed that the product, price, promotion, service, and place/location variables simultaneously determined purchase decision. Partially, product and place/location variables determined positively and significantly towards purchasing decisions, while price, promotion, and service variables did not affect purchase decisions. Future research can be carried out using the campus brand as a mediating variable.